The nutrient status of paddy fields is based on the results of the analysis of the Rice Soil Test Device (RSTD) in Jerukagung Village, Klirong District, Kebumen Regency. - Nurlaila Fatmawati; Heri Setyawan; Toni Haryanto (Akademi Komunitas Perkebunan Yogyakarta, 2023)
This study aims to determine the nutrient status of the soil and obtain fertilization recommendations based on the results of the analysis of the Rice Soil Test Device (RSTD) in Jerukagung Village, Klirong District, Kebumen Regency. Data collection was carried out by data analysis with RSTD, direct interviews and distribution of questionnaires to farmers who own rice fields. Sample selection is carried out by random sample method (probability sampling). The number of samples taken by 30 farmers from 4 farmer groups who have paddy fields in Jerukagung Village, Klirong District, Kebumen Regency.Based on the test results using RSTD, with a low N content (86.67%) so it needs to be fertilized 250 kg of Urea / ha. The P content is high (86.67%) so it needs to be fertilized 50 kg SP-36/ha. The K content is medium (73.33%) so it needs to be fertilized 50 kg KCl / ha or by using straw as much as 5 tons / ha. The degree of acidity or pH in general is neutral (60%), which is in the range of pH 6-7 so that the recommendation for N fertilization is in the form of Urea with a conventional drainage system.